Zakat Perusahaan Daerah Air Minum Tirto Panguripan Kabupaten Kendal Perspektif Maqāṣid Syarī’ah - Kumala, Irma Nur; Bashori, Akmal (At-Ta’awun: Jurnal Mu’amalah dan Hukum Islam, 2022)
The management of corporate zakat in the maqashid sharia perspective is the management of corporate zakat that refers to the goals of sharia so that maslahah is achieved among the people. The existence of this research is expected to be a small step that bridges the community to better understand the company's zakat. The purpose of this study is so that writers and readers can better understand the company's zakat. This research is a qualitative research that is outlined in a description, after going through a series of data searches from direct and indirect sources. Direct research was conducted by interviewing the Kendal Regency BAZNAS as the zakat management agency and the PDAM as muzaki. From this study, the researchers obtained the following results: first, the management of company zakat from the Panguripan Regional Drinking Water Company, Kendal Regency by the National Amil Zakat Agency of Kendal Regency, was implemented in the orphanage compensation program and the distribution of SR or clean water channels for families who less fortunate. Second, the company’s zakat utilization program is included in the maqashid sharia dzaruriyyat group because it relates to primary human needs. These programs cover several criteria for the dzaruriyyat group, namely hifdzu ad-din, hifdzu an-nafs, hifdzu al-aql, hifdzu an-nasl and hifdzu al-mal.